2008
DOI: 10.1016/j.molcel.2008.03.018
|View full text |Cite
|
Sign up to set email alerts
|

DAP5 Promotes Cap-Independent Translation of Bcl-2 and CDK1 to Facilitate Cell Survival during Mitosis

Abstract: DAP5 is an eIF4G protein previously implicated in mediating cap-independent translation in response to cellular stresses. Here we report that DAP5 is crucial for continuous cell survival in nonstressed cells. The knockdown of endogenous DAP5 induced M phase-specific caspase-dependent apoptosis. Bcl-2 and CDK1 were identified by two independent screens as DAP5 translation targets. Notably, the activity of the Bcl-2 IRES was reduced in DAP5 knockdown cells and a selective shift of Bcl-2 mRNA toward light polysom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
135
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(141 citation statements)
references
References 44 publications
4
135
2
Order By: Relevance
“…Accordingly, recent reports have shown that p97 stimulates c-myc IRES activity in vitro (Hundsdoerfer et al 2005), enhances capindependent translation of pro-survival factors during mitosis (Marash et al 2008), and modulates alternative translation initiation during endoplasmic reticulum stress (Lewis et al 2008). Thus, p97 and Ct may exert similar effects on cap-independent translation of c-myc or VEGF mRNA in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, recent reports have shown that p97 stimulates c-myc IRES activity in vitro (Hundsdoerfer et al 2005), enhances capindependent translation of pro-survival factors during mitosis (Marash et al 2008), and modulates alternative translation initiation during endoplasmic reticulum stress (Lewis et al 2008). Thus, p97 and Ct may exert similar effects on cap-independent translation of c-myc or VEGF mRNA in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports established the neuroprotective effect of Bcl-2 in neurons. [61][62][63] HuR has also been linked to the activation of prosurvival Bcl-2 family members 56,64,65 through the regulation of their turnover and translation, 56,[66][67][68] In HT-22 cells, HuR maintains Bcl2 mRNA stability and translation at a constant rate to buffer its requirement during assault and preserve mitochondrial homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…cDNA was measured by q-RT-PCR using the QuantiTect SYBR Green PCR Kit (Qiagen). Primers were designed from previous publications; for p53, 18 Bcl-2 17 and DAP5, 17 glyceraldehyde 3-phosphate dehydrogenase (GAPDH) mRNA levels served as an endogenous control. All real-time q-RT-PCR experiments were performed in triplicate with no-template as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…15,16 It has been reported that DAP5 regulates IRES-driven translation of Bcl-2 (B-cell lymphoma 2), p53, XIAP (X-linked inhibitor of apoptosis protein), CDK1 (cyclin-dependent kinase 1), c-Myc and other IRES-containing genes under conditions of stress, growth and apoptosis. [17][18][19] DAP5 mRNA also contains an IRES in its 5′-UTR, and is proficient in promoting its own translation, generating a positive feedback loop for its expression. 14,15 Additionally, DAP5 may undergo post-translational modifications, such as cleavage by caspases during apoptosis, generating a truncated, yet functional 86-kDa form of DAP5 that is more potent and efficient at translation initiation.…”
mentioning
confidence: 99%